Deprescribing Proton Pump Inhibitors in an Academic, Primary Care Clinic: Quality Improvement Project. Issue 10 (November 2020) - Nallapeta, Naren; Reynolds, Jessica L.; Bakhai, Smita
Abstract : Goal: The goal of this study was to reduce the percentage of inappropriately prescribed proton pump inhibitors (PPIs) in patients aged 50 and older from 80% (baseline) to 60% within 12 months in an academic, internal medicine clinic. Background: The use of PPIs has increased drastically worldwide. Internal medicine clinic patients had inappropriate use of PPIs for an average of 4 to 5 years. Study: A multidisciplinary quality improvement team used the Plan-Do-Study-Act Model of health care improvement and performed a root cause analysis to identify barriers to inappropriate use of PPIs. The outcome measure was the percentage of patients inappropriately prescribed PPI. Process measures were completion rates of PPI risk assessment and esophagogastroduodenoscopy. Interventions included the creation of customized electronic health record templates and education to providers and patients. Analysis was performed using monthly statistical process control charts. Results: The average rate of PPI discontinuation was 51.1% (n=92/180), which corresponds to 30.0% inappropriate PPI usage within 12 months. The mean PPI discontinuation rate in the 1-year prestudy, study and 6 months poststudy period was 2.0%, 32.0%, and 49.7%, respectively. The mean esophagogastroduodenoscopy completion rate was 49.8% from the baseline of <30%. Conclusions: We achieved a statistically significant and sustainable reduction of inappropriate PPI use to 30% from the baseline rates of 80% and surpassed our goal within 12 months. This quality improvement was unique as no pharmacy personnel was utilized in this process. The multifaceted strategies in a safety-net internal medicine clinic resulted in successful deprescribing of PPI and can be replicated in other setting.